PENGUASAAN KOMPETENSI PEDAGOGIK GURU TERSUPERVISI KLINIS DAN GURU TANPA SUPERVISI DI DUA SMA SWASTA DI KOTA AMBON - Leinora Juliana Kaipatty; Lobby Loekmono; Slameto Slameto (Kelola: Jurnal Manajemen Pendidikan, 2015)
This study is an experimental research with using pretest and posttest control group design. The aimed of the study were: 1). To know the differences significant of teacher’s mastery of pedagogical competences between teachers clinical supervised in SMA Kristen YPKPM Ammbon and non-supervised teachers in SMA Kartika XIII-I Ambon, 2). To determine how the the clinical supervision influenced the teachers’ mastery of pedagogical competences. The data was collected by using observation toward teaching profile competence from Wasserman and Egert. Data analyzed using t test comparative and linear regression analysis. The result of the study was the coefficient t test was 4,184 with significant 0,001 < 0,05. It proved that there was a difference between supervision and non-supervision teachers significantly. The clinical supervision has influence about 41,9% on teachers pedagogical competences.